Long-term renal function alterations in hepatitis C patients with SVRs: Impacts of therapies and mixed cryoglobulinemia - Ming-Ling Chang; Jur-Shan Cheng; Wei-Ting Chen; Chao-Wei Hsu; Kuan-Hsing Chen; Yung-Chang Chen; Rong-Nan Chien (Journal of Infection and Public Health, 2024)
Background / Aims: Effects of anti-hepatitis C virus (HCV) therapeutic regimens and mixed cryoglobulinemia on long-term renal function of HCV-infected patients with viral clearance have not been determined. Methods/Materials: A prospective 10-year cohort study of 1212 HCV-infected patients (interferon-based therapy, n = 615; direct-acting antiviral (DAA) therapy, n = 434) was conducted. Results: At baseline, age, body mass index (BMI), hemoglobin (Hb) and uric acid (UA) levels, and fibrosis-4 score were associated with estimated glomerular filtration rates (eGFRs) in HCV-infected patients. At 24 weeks posttherapy, age, BMI, and Hb and UA levels were associated with eGFRs in patients with a sustained virological response (SVR) (n = 930). Compared with those at baseline, the eGFRs were lower in SVR patients at 24 weeks posttherapy, regardless of the therapeutic regimen. The eGFRs reverted to baseline levels in interferon-treated SVR patients up to 10 years posttherapy but remained decreased in DAA-treated SVR patients up to 4 years posttherapy. Longitudinally, repeated measures analyses with generalized estimating equations showed that the interactions between DAA-based therapy and mixed cryoglobulinemia (OR: 3.291) and Hb levels (1.778) were positively, while DAA-based therapy (0.442), age (0.956), UA levels (0.698), homeostasis model assessment-insulin resistance index (0.961) and complement 4 levels (0.9395) were negatively associated with the eGFR. Among DAA-treated SVR patients, the baseline eGFR (OR: 1.014; 95%CI OR: 1.004–1.023) and high-sensitivity C-reactive protein (HR: 1.082; 95%CI HR: 1.018–1.15) were associated with eGFR reduction at 24 weeks and 4 years posttherapy, respectively. Conclusions: Hepatic fibrosis was an HCV-related factor for renal function. Longitudinally, DAA therapy was negatively, while the interaction between DAA therapy and mixed cryoglobulinemia was positively associated with renal function in SVR patients; deteriorated renal function was recovered in interferon-treated SVR patients. Particularly in DAA-treated SVR patients, baseline renal function and systemic inflammation were associated with short- and long-term reductions in renal function, respectively.